Tingkat Kemampuan Bahasa Inggris Mahasiswa Program Kebidanan - Fibri Indira Lisanty (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
The purpose of this study is to determine the level of English proficiency in the midwifery study programme in 2024. This research uses descriptive quantitative research methods with the aim of providing a description or descriptive of a situation objectively using numbers. This research uses Purposive Sampling technique to determine the sample. The selection of research samples that can help researcher provide the best information. Based on the results of the study, it was found that the level of English language skills of midwifery study programme students in semester 6 had a good level. It is proven by the data shows that The overall score of the accumulated scores of twenty respondents is one thousand five hundred and twenty. Where the score is worth an average of 76. From the average value of 76. from the results of the study, the largest percentage is 55% where the calcification of the percentage is average or average with a frequency of 11 respondents while the smallest percentage is 5% with a very good classification. A total of 1 respondent.